Primary Follicular Lymphoma of the Duodenum with Erosions as Atypical Macroscopic Features - Keiko Takeuchi; Masaya Iwamuro; Atsushi Imagawa; Yoshitsugu Kubota; Katsuya Miyatani; Katsuyoshi Takata; Hiroyuki Okada (Case Reports in Medicine)
A 52-year-old Japanese woman who was eventually diagnosed with primary follicular lymphoma of the duodenum showed atypical endoscopic features, namely, erosions with peripheral whitish edematous mucosa. Initial biopsy specimens taken from the erosions revealed insufficient numbers of lymphoma cells for histological diagnosis. Subsequent biopsy specimens from the peripheral mucosa containing the whitish enlarged villi showed infiltration of the lymphoma cells forming lymphoid follicles, which led us to the appropriate diagnosis. This case indicates that endoscopists should take biopsy samples from the peripheral mucosa with whitish enlarged villi rather than erosions in the rare instances that erosions appear as the main macroscopic feature of intestinal follicular lymphoma.